Students’ Perception on the Use of AI Paraphrasing Tools in Writing Research Proposal - Mahmud, Nurul Inayah; Saud, Indah Wardaty (Journal of English Language Teaching, Linguistics, and Literature Studies, 2024)
The use of AI Paraphrasing Tools in education creates a conflict. These tools offer potential benefits for student writing, but their improper use raises serious concerns about plagiarism. This study aims to investigate students' perceptions of AI paraphrasing tools in research proposal writing. The scope of this research includes the advantages and disadvantages of AI paraphrasing tools. The participants of this study were 23 students from the English Language Education Program at the State Islamic Institute of Manado for the 2020/2021 academic year. This study employed a qualitative research method, and the researcher distributed a questionnaire to the students as an instrument. The questionnaire included 15 open-ended questions on Google Forms. The findings indicate that many students recognize the efficiency and convenience provided by these tools. They highlighted how AI paraphrasing tools can save time, improve content clarity, and assist in avoiding plagiarism. However, this study also revealed some drawbacks associated with the use of AI paraphrasing tools. The primary concern expressed by students was the potential of these tools to misinterpret the original meaning, resulting in inaccuracies and loss of context. Additionally, students noted that excessive reliance on these tools might diminish their critical thinking and creativity, ultimately hindering the development of their writing skills.Keywords: Writing, Research Proposal, AI Paraphrasing Tools